Evaluation of Information Technology Management Roles in Sales Food Industries Case Study food CompaniesKhorasan Razavi - Mashhadi, Mostafa; Tehrani, Mostafa Mazaheri; Porsalimi, Mojtaba (Ciência e Natura, 2015)
While many quality products should be only a short time in the market such as, and must give way to the final product tastes, preferences and needs of customers are compatible. Neglect or failure to timely delivery to our customers' requests may be too expensive. These conditions have caused the issue is important information for manufacturing organizations. The purpose of this study was to investigate new methods of information technology, sales of food industry in Iran, with manufacturing units of Khorasan, as a major hub for food production in the country. A questionnaire was developed for this study. Application information technology management by studying four parameters affecting the sale: Official Website, Internet sales of electronic business, Internet advertising and social networking As well as customer relationship management, field tested and evaluated. The results of field research 50 companies in various industries, including: Milk and dairy products, Beverages, Canning and juice, Meat and meat products, Cereal and flour products, Fermentation industry, Additives and spices the target population has been concluded. The results show that if Management of information technology (IT) as a principle and right of sale system used food factories Makes it easy to customer order, reduce the costs of marketing and advertising, and increasing the efficiency of product produced.